The TRHDE and TSHR Genes Regulate Laying Traits in Domesticated Zi Geese - Xiuhua Zhao; Shan Yue; Yuanliang Zhang; Jinyan Sun; Fugang Peng; Zhenhua Guo (Current Issues in Molecular Biology)
Domestic geese are typically seasonal breeders, and the timing and number of eggs they lay vary depending on the region and breed. Previous studies evaluated the Zi goose, which is currently the domestic goose breed with the highest egg production. This research divided the reproductive cycle into four periods and compared the ovarian RNA-seq and DNA methylation data of Zi geese across these time points to identify the key genes that increase egg production. By integrating differentially expressed genes and differentially methylated genes, we identified 525 candidate genes that presented upregulated expression and hypomethylated regions (the hypo-up group). Ultimately, we found that the thyrotropin-releasing hormone degrading enzyme (TRHDE) and thyroid-stimulating hormone receptor (TSHR) genes play a crucial role in regulating the reproductive cycle of Zi geese. We also generated a proposed model of the relationship between the TRHDE and TSHR genes in Zi geese. This study provides theoretical references for the development of egg-laying goose breeds and raises additional scientific questions for further discussion among researchers.